A STUDY ON STUDENTS’ ANXIETY AND ITS CORRELATION WITH THE SPEAKING PERFORMANCE OF XI GRADE STUDENTS AT SMAN 1 KRIAN - PUTRI, PRAMESTHI LAKSHITA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Foreign Language Learning, Speaking, Anxiety, SMAN 1 KRIAN English has become the most dominant global language which should be mastered by all students in Indonesia. Mastering new grammatical rules, pronunciation, and vocabulary, makes foreign language learning a new big challenge for people who study it. One of the big challenges when learning English is speaking. Usually students have difficulty in speaking performance. Soit will increase their anxiety. This study was aimed at finding out the anxiety levels of XI grade students, the factors that affect the anxiety and correlationbetween students’ anxiety and the speaking performance of XI grade students of SMAN 1 KRIAN. This study used quantitative and qualitative approach since the data were in the form of numbers and word. The quantitative data used in this research were the result of Foreign Language Anxiety Classroom Scale questionnaires filled by XI grade students at SMAN 1 KRIAN, and the result of speaking performance. While the qualitative data used in this research were the result of interview. The researcher collected the data by choosing Foreign Language Classroom AnxietyScale, distributing the questionnaire to 56 students, collecting the result of questionnaire, selecting 4 students with high anxiety level and 4 students with low anxiety level, asking them to tell a story and deliver speech, scoring, andinterviewing the participants about their speaking performance. Thus, theresearcher analyzed them and finally drew a conclusion.  The researcher found that there was high anxiety level in XI Social students. The factors that affect students’ anxiety namely communication apprehension, test anxiety, and fear of negative evaluation. The researcher also found significant positive correlation in XI Social between students who have low anxiety score and the speaking performance. There was significant negative correlation between XI Social between who have high anxiety score and the speaking performance.The conclusion was anxiety gave influence to the student’s speaking performance. For the next researcher, it is recommended to conduct the study ofanxiety using other theories. The researcher also suggests the next researchers to examine the relationship between speaking anxiety and academic achievement by using different instrument.